Redesign Kompor Ergonomis Menggunakan Konversi Bahan Bakar Dengan Metode Value Engineering - M Abid Hamami; Satriardi Satriardi; Ari Andriyas Puji (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2020)
The use of stoves that are not ergonomic becomes an obstacles for food seller because it can interfere with physical comfort while working due to inflexsible stove conditions for use. Therefore, this research will identify the data nedeed, provide suggestions for an ergonomic stove design in form of 3 dimensions and be directly applied in tangible form using the value engineering method. The stages used are information stage, creaativity stage, analysis stage (creative analysis, raw material costs, anthropometry, and raw material analysis). Anthropometry data was obtained from 135 of pecel lele seller in Pekanbaru in form of dimensions of elbow span in standing position (D33), upper arm length dimensions in sitting position (D23), and height dimensions of vertebrae in standing position (D6). The next stage is development and reccomendations stages.and the last stage is analysis stage ofrom result of design. The result obtained that the elbow in the standing position (2x D33) = 2x 66.6 cm = 133.2cm, the length of the upper arm in the sitting position (D23) = 40.0 cm, and the height of the vertebrae in the standing position (D6) = 75.2cm